Echographic and Kinetic Changes in the Shoulder Joint after Manual Wheelchair Propulsion Under Two Different Workload Settings - Gil-Agudo, Ángel; Solís-Mozos, Marta; Crespo-Ruiz, Beatriz; del-Ama Eng, Antonio J.; Pérez-Rizo, Enrique; Segura-Fragoso, Antonio; Jiménez-Díaz, Fernando (Frontiers in Bioengineering and Biotechnology, 2014)
Abstract Manual wheelchair users with spinal cord injury have a high prevalence of shoulder pain, due to the use of the upper extremity for independent mobility, transfers and other activities of daily living. Indeed, shoulder pain dramatically affects quality of life of these individuals. There is limited evidence obtained through radiographic techniques of a relationship between the forces acting on the shoulder during different propulsion conditions and shoulder pathologies. Today, ultrasound is widely accepted as a precise tool in diagnosis, displaying particularly effectiveness in screening the shoulder rotator cuff. Thus, we set out to perform an ultrasound-based study of the acute changes to the shoulder soft tissues after propelling a manual wheelchair in two workload settings. Shoulder joint kinetics was recorded from 14 manual wheelchair users with spinal cord injury while they performed high and low intensity wheelchair propulsion tests (constant and incremental). Shoulder joint forces and moments were obtained from inverse dynamic methods, and ultrasound screening of the shoulder was performed before and immediately after the test. Kinetic changes were more relevant after the most intensive task, showing the significance of high intensity activity, yet no differences were found in ultrasound-related parameters before and after each propulsion task. It therefore appears that further studies will be needed to collect clinical data and correlate data regarding shoulder pain with both ultrasound images and data from shoulder kinetics.